Benjamin V. Cohen : architect of the New Deal - Lasser, William (Yale University Press, 2002)
A key figure in the administrations of Franklin D. Roosevelt and Harry S. Truman, Benjamin V. Cohen (1894-1983) was a major architect of public policy from the first days of FDR's presidency through the early days of the Cold War. Although he kept a low public profile, Cohen's influence extended across a wide range of domestic and foreign policy initiatives. This biography offers an account of Ben Cohen's life and career, and an assessment of his contribution to the origin and development of modern American liberalism.